The trauma burden on a tertiary surgical intensive care unit during the lockdown period in South Africa: A retrospective observational study. (October 2022) - van Zyl, Albert GP; Ahmed, Nadiya; Davids, Ryan
Background: Trauma places a significant burden on scarce South African critical care resources. The impact of the lockdown period in 2020 on these resources has not been studied. Restrictions on citizen movement and alcohol sales during the lockdown period presented a unique time period to investigate the burden of trauma on a low–middle-income country tertiary hospital intensive care unit. Methods: A retrospective observational analysis of all patients admitted to a tertiary hospital surgical intensive care unit during the lockdown period in 2020, compared to the same time period in 2019 and 2018. Data were analysed to detect if a significant difference was present in the number of trauma admissions, length of stay and mechanisms of trauma. Results: A significant decrease in the number of trauma admissions to ICU in 2020 was observed as compared to 2018 and 2019 during the same period ( p = <0.001), with a reduction of nearly 50%. The incidence of trauma admissions was lower in all individual lockdown levels in 2020 as compared to 2018 and 2019, and the lowest incidence was recorded in level 5 of 2020. There was no difference among the length of stay of trauma patients in ICU in 2018, 2019 and 2020. There was no difference between the incidence of trauma admissions during lockdown level 3 (with and without alcohol sales) in 2020 compared to 2018. The profile of penetrating and non-penetrating trauma over the 3 years was the same ( p = 0.22). There were no interactions between years, lockdown periods and penetrating trauma ( p = 0.22). Interpretation: There was a significant decrease in the trauma burden presented to the surgical ICU during the lockdown period in 2020. Levels with the strictest restrictions on movement and alcohol use had the greatest measurable impact. The decreased number of trauma patients admitted in 2020 was comparable to the national trend of decreased trauma numbers recorded in all levels of the national healthcare system.